Analisis Peran Financial Technology (QRIS) Dalam Meningkatkan Literasi Keuangan (Studi Kasus Pada Toko Athira) - Jumria .; Sasmita Nabila Syahrir; Nichen . (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Digital financial technology has expanded rapidly across Indonesia's MSME sector, with QRIS emerging as the leading cashless payment channel; whether this expansion also strengthens the financial literacy of micro-enterprise owners in rural trading areas remains underexamined. This study aims to examine how QRIS contributes to the financial literacy of a micro-enterprise owner, focusing on whether the transaction data it generates is understood, retrieved, and applied to bookkeeping, cash-flow monitoring, and decision-making. A qualitative case-study design was used, drawing on three informants—the owner and two employees—through in-depth interviews, observation, and documentation of QRIS reports, analyzed with the Miles, Huberman, and Saldaña model and strengthened through source triangulation. Findings show that although Toko Athira has used QRIS since 2024, its use has stayed confined to processing transactions; the automatically generated sales recapitulations have never been reviewed for bookkeeping, cash-flow tracking, or sales evaluation, and financial records continue to be kept manually in a simple notebook. The study concludes that adopting digital payment technology alone does not automatically raise financial literacy unless owners also develop the capacity to interpret and use the resulting financial information, pointing to a pressing need for structured literacy training so QRIS becomes a managerial tool, not merely a payment channel.